Recent trends in multimedia information processing : - Liatsis, Panos (World Scientific, 2002)
Proceedings of the 9th Intl Workshop on Systems, Signals and Image Processing, held November 7-8, 2002 in Manchester Town Hall, U.K. Reports on the state of the art in multimedia information processing. The areas of interest include video/ image coding, color vision, 3D reconstruction, field programmable devices, and many others.